Pengaruh Frekwensi Pemberian Kompos NT45 dan Dosis Urea terhadap Pertumbuhan dan Hasil Kacang Tanah (Arachis hypogaea L.) di Ultisol - NILLA KRISTINA; MUHSANATI MUHSANATI; SARDI PADAPOTAN.S (Agrotrop : Journal on Agriculture Science, 2016)
Effect of Application Frequency of NT45 and Urea Fertilizer on Growth and Yield ofPeanut. The productivity of peanut in Indonesia was decline in last year because of thechanging of the land function especially in Java. We need to find the new area for peanut.And one of them is Ultisol that is marginal land. The peanut productivity in Indonesian is stilllow because of that we have to improve our cultivation technique especially on Ultisol. Theaimed of this research was to find best combination between NT45 organik fertilizer and Ureafertilizer dosage for increasing growth and yield of the peanut. The research was conducted inFactorial 3 x 3 in Randomized Completely Design with three replications. The first factor wasfrequency of giving NT45 consisted of two level : once and twice giving. The second factorwas Urea fertilizer dosage consisted of three levels : 25 kg/ha (B1), 50 kg/ha (B2) and 75kg/ha (B3). The result showed that pod production of peanut was lower on giving 25 kg/haUrea than NT45 and Urea. Once (20 ton/ha) and twice application (40 ton/ha) NT45 organikfertilizer showed that the result of pod and grain yield were the same. On dossage 50 kg/Ureagave best pod yield on Ultisol.